Does the implant-abutment interface interfere on marginal bone loss? A systematic review and meta-analysis - Enéias Carpejani ROSA; Tatiana Miranda DELIBERADOR; Tuanny Carvalho de Lima do NASCIMENTO; Cibele Cândida de Almeida KINTOPP; Juliana Shaia Rocha ORSI; Letícia Maíra WAMBIER; Sharukh Soli KHAJOTIA; Fernando Luis ESTEBAN FLOREZ; Carmen Lucia Mueller STORRER (Brazilian Oral Research)
Abstract The objective of this systematic review was to compare the conical internal connection (IC) with the external hexagonal connection (EH) on the occurrence of marginal bone loss (ΔMBL). Different databases were used to carry out the selection of the elected studies. The studies were judged according to the risk of bias as “high”, “low” and “unclear” risk. For the meta-analysis we included only studies that could extract the data of ΔMBL, survival rate (SR) and probing depth (PD). No statistically significant differences were found for ΔMBL data at one, three- and five-year survival rates between implant connections (p <0.05), however statistically significant differences were found for PD between EH and IC implants (1-year follow-up) -0.53 [95%CI -0.82 to -0.24, p = 0.0004]. This present systematic review demonstrated that there are no significant differences between IC and EH implants for both ΔMBL and SR at 1, 3 e 5 years after functional loading, although better PD values were observed for implants pertaining to the IC connections. Considering the high heterogeneity, more well-delineated, randomized clinical trials should be conducted.